A comparative study on the decalcifying effect of a softdrink with fluoride and that with phosphate - Dela Cruz, Lillie Joyce
This paper aims to compare the inhibiting action of fluoride and phosphate against the decalcifying effect of a popular beverage, specifically 7-Up. Sound teeth were placed in three sets of immersion media namely: untreated 7-Up, 7-Up with Fluoride, and 7-Up with Phosphate. To quantify the amount of enamel decalcification, the samples were subjected to the Atomic Absorption Spectroscopy analysis for Calcium determination after tooth immersion. The results showed that Fluoride has a greater protective action against decalcification than Phosphate.